SIGNIFIED AND SIGNIFIER ON MORALITY MEANING IN “MEMBASUH” SONG LYRICS BY HINDIA FT. RARA SEKAR - Yuani Nurdwi Kaesari; Nur Sakinah, Myrna (JURNAL ILMU BUDAYA, 2023)
This article aims to analyze the moral meaning in the song lyrics of "Membasuh" by Hindia in collaboration with Rara Sekar. The method of research used in this article is interpretative qualitative research. This research used the method of analyzing symbols. In this research, the song is analyzed based on every stanza; the signifier is the song lyrics of "Membasuh", and the signified is the interpretation of meaning from the lyrics. On the basis of the findings, the writer found the meaning of morality in the song lyrics of "Membasuh" in every stanza. The writer found a lot of messages related to morality, both good and bad. It can be seen in every stanza that the songwriter tries to portray his or her thoughts on morality, whether they are good or bad. The song lyrics contain a lot of moral meaning, especially the good ones.